USING THE ANALYTICAL HIERARCHY PROCESS ALGORITHM FOR ASSESSMENT OF LECTURER PERFORMANCE BASED ON LECTURER EVALUATION - Helma Widya; Hermansyah Alam; Selfitrida A. Yani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Lecturer performance appraisal in general aims to provide feedback to lecturers in an effort to improve their performance, in increasing the productivity of an organization, and specifically related to various policies towards lecturers, such as promotions in rank or class, promotions, salary adjustments, training and development, planning career, behavior improvement and others. The role of a decision support system will assist management in achieving the objectives of lecturer performance appraisal, such as lecturer career planning, without compromising the parameters that have been determined. The AHP (Analytical Hierarchy Process) method approach is used in designing a structured system with programming language using PHP and MySQL Databases. The system created can be used to help facilitate the head of study programs or academic bureaus in deciding the problems encountered during the lecturer performance appraisal process. then determine the lecturer's performance assessment with the weighted value of all the criteria for each lecturer, and the head of study program or academic bureau can make decisions and policies for assessing the lecturer's performance. Keywords: Lecturer Performance Assessment, Analytic Hierarchy Process (AHP), Decision Support System